Effect of geotextile reinforcement on cyclic undrained behavior of sand. Issue 104 (January 2018) - Ziaie Moayed, Reza; Alibolandi, Mahdi
Abstract: Dynamic behavior of reinforced soil are evaluated relative to a number of factors including: strain level, density, number of cycles, material type, fine content, geosynthetic inclusion, saturation, and effective stress. This paper investigates the dynamic behavior of saturated reinforced sand under cyclic stress condition. The cyclic triaxial tests are conducted on remolded specimens under various cyclic stress ratios (CSR) which reinforced by different arrangement of non-woven geotextile. Aforementioned tests simulate field reinforced saturated deposits during earthquake or other cyclic loadings. This analysis revealed that the geotextile arrangement played dominant role on dynamic soil behavior and as geotextile close to top of specimen, the liquefaction resistance increased. Meanwhile, the results demonstrate that the effects of arrangement of reinforcement layers on deformation and shear modulus are considerable. Highlights: The geotextile reinforcement enhances the maximum shear and axial modulus of the undrained soil. The geotextile inclusion changes ductile behavior of sand to a more brittle one. The geotextile arrangement played dominant role on the dynamic soil behavior. The presence of geotextile leads to increasing the undrained cyclic strength of soil.